2020
DOI: 10.1136/bmjopen-2020-042183
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of professional competence in Ireland: a national survey of doctors’ attitudes and experiences

Abstract: ObjectivesProgrammes to ensure doctors’ maintenance of professional competence (MPC) have been established in many countries. Since 2011, doctors in Ireland have been legally required to participate in MPC. A significant minority has been slow to engage with MPC, mirroring the contested nature of such programmes internationally. This study aimed to describe doctors’ attitudes and experiences of MPC in Ireland with a view to enhancing engagement.ParticipantsAll registered medical practitioners in Ireland requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The barriers highlighted by doctors in this study are broadly in line with those found by another recent study based in Ireland. 23…”
Section: Theme 4: Workplace Challengesmentioning
confidence: 99%
“…The barriers highlighted by doctors in this study are broadly in line with those found by another recent study based in Ireland. 23…”
Section: Theme 4: Workplace Challengesmentioning
confidence: 99%
“…The medical field is considered to have the most quickly evolving knowledge. 1 Medical professionals need to master the latest medical technologies and methods to maintain professional competence 2 and better serve patients. 3 A decline in physicians' knowledge with time may result in lower quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Most mixed‐methods studies involved surveys with quantitative and qualitative components. Seventeen studies integrated theory in the design and/or analysis of the research 26,39–54 . Theories applied included those focused on process change, societal control and regulation and individual behaviour change 23,55–57 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Requirements imposed by regulatory authorities, employers and health care associations were the dominant extrinsic motivator for engagement with MPC 25,47,61,65,68,72,80–82 . Conversely, patient and colleague expectations and perceptions were not strong extrinsic motivators for participation in the process 47–50,81,83 . A few studies' participants did think that MPC was important to their patients 61,62,84,85 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation